Gastrointestinal effects of general anaesthesia in horses undergoing non abdominal surgery: focus on the clinical parameters and ultrasonographic images. (June 2019) - Salciccia, Alexandra; Gougnard, Alexandra; Grulke, Sigrid; de la Rebière de Pouyade, Geoffroy; Libertiaux, Vincent; Busoni, Valeria; Sandersen, Charlotte; Serteyn, Didier
Abstract: The ultrasonographic images of the gastrointestinal tract in horses can be influenced by fasting and sedation but the proper effect of general anaesthesia (GA) on them has not been determined yet. This study aimed to evaluate the effects of GA on ultrasonographic images of the gastrointestinal tract in horses and to compare these effects with a clinical evaluation. Twenty horses undergoing non-abdominal surgeries were evaluated by ultrasonography before and 4 times within 24 h after GA. Each ultrasonographic exam focused on the stomach, the duodenum and on 5 locations on the jejunum. The four-quadrant auscultation and the postoperative faecal output were also recorded. Pre and post anaesthetic values were compared using linear mixed effects models. None of the horses presented colic signs or reduced faecal output. During the first 2 post anaesthetic evaluations, the gut sounds were significantly decreased and, when taking all jejunal locations together, the jejunal diameter and visualisation frequency significantly increased. No intestinal loop appeared thickened and most of their diameters remained within the normal range. Our results suggest that the effects of GA on the ultrasonographic images of the small intestine are mild and of short duration and can therefore be differentiated from a pathological process. Highlights: Jejunal visualisation and diameter were increased within 2–4 h after anaesthesia. Almost all maximal diameter of small intestine were within normal limits. No small intestinal loops appeared thickened after anaesthesia. The gut sounds were significantly reduced within 2–4 h after general anaesthesia. No horse showed reduced fecal output or colic signs after anaesthesia.